The impact of internal and macroeconomic factors on the profitability of the banking sector. A case study of the Western Balkan countries - Arsim Hoxha; Roberta Bajrami; Ylber Prekazi (Business: Theory and Practice, 2025)
The banking sector in the Western Balkan countries has changed dramatically in recent years. A variety of factors have contributed to these changes, such as economic growth, increased competition, and the implementation of new regulations. As a result, the profitability of the banking sector varies greatly between countries. The purpose of this research is to look into the impact of internal and macroeconomic factors on the profitability of the banking sector in the Western Balkan countries. The research used 85 observations from unbalanced panel data from five countries from 2005 to 2021. Data were gathered from the International Monetary Fund’s World Economic Outlook Database, which contains information on the trend and progress of banking in the Western Balkans. The variables used included macroeconomic variables, internal bank variables, and industry variables, with return on assets and return on equity used to measure bank profitability. Panel regression with pooled least squares, fixed effects, and random effects was used to analyze these variables. Internal factors such as bank Z-score, 3-bank asset concentration, bank net interest margin, bank overhead costs to total assets, bank credit to deposits, and bank capital to total assets have a positive impact on profitability, according to the findings. GDP and inflation, for example, have a mixed impact on profitability. The impact of industry factors such as liquid assets, deposits, and short-term funding, as well as bank Z-score, on profitability is mixed. The study’s findings have significant implications for policy experts and bank managers in Western Balkan countries. The findings can be used by policymakers to create policies that promote the profitability of the banking sector. The findings can be used by bank managers to improve their banks’ profitability by making strategic decisions about asset allocation, capital structure, and risk management.